2006
DOI: 10.1136/jmg.2006.044313
|View full text |Cite
|
Sign up to set email alerts
|

Schimke immuno-osseous dysplasia: a clinicopathological correlation

Abstract: Background: Schimke immuno-osseous dysplasia (SIOD) is a fatal autosomal recessive disorder caused by loss-of-function mutations in swi/snf-related matrix-associated actin-dependent regulator of chromatin, subfamily a-like 1 (SMARCAL1). Methods: Analysis of detailed autopsies to correlate clinical and pathological findings in two men severely affected with SIOD. Results: As predicted by the clinical course, T cell deficiency in peripheral lymphoid organs, defective chondrogenesis, focal segmental glomeruloscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Additional features include hypothyroidism, abnormal dentition, bone marrow failure, thin hair, corneal opacities, arteriosclerosis, cerebral ischemia, and migraine-like headaches [2–5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional features include hypothyroidism, abnormal dentition, bone marrow failure, thin hair, corneal opacities, arteriosclerosis, cerebral ischemia, and migraine-like headaches [2–5]. …”
Section: Introductionmentioning
confidence: 99%
“…FSGS is the predominant renal pathology and is refractory to treatment with glucocorticoids, cyclosporine A, and cyclophosphamide [4, 6]. Suggesting a cell autonomous mechanism for the renal disease, renal transplantation is efficacious, and the disease does not recur in the graft [2, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…CVS abnormalities: Vascular abnormalities occur in many patients, including transient ischemic attacks and (or) cerebral ischemia, putatively secondary to early onset, and progressive arteriosclerosis (Boerkoel et al 2000;Clewing et al 2007). A recent study among more than 50% of SIOD patients found arteriosclerosis associated with vascular intimal and medial hyperplasia, smooth muscle cell hyperplasia, and fragmented and disorganized elastin fibers (Morimoto et al 2012).…”
Section: Schimke Immuno-osseus Dysplasiamentioning
confidence: 99%
“…This gene encodes a protein involved in chromatin remodeling, but the pathogenic mechanism of SIOD is still unclear (Clewing et al 2007). …”
Section: Schimke Immuno-osseus Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation